2008
DOI: 10.3174/ajnr.a1324
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Coiling of Cerebral Aneurysms Using “Bioactive” or Coated-Coil Technologies: A Systematic Review of the Literature

Abstract: SUMMARY: Second-generation coils have been available since 2002. We wanted to assess their performance and appraise available evidence. Therefore we performed a systematic review of the literature from 2002 to 2007. There were 27 studies with a total of 2390 patients that met pre-specified inclusion criteria. All studies were classed as having a high risk of bias. There were no randomized trials and for most studies results were not independently assessed and follow-up periods were short (mean 7 months). There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 45 publications
2
34
0
1
Order By: Relevance
“…20 HydroCoils are safe, and initial procedural results from the HELPS study showed no significant difference in the complication rate in a properly controlled study. 21 This study agrees with ours in demonstrating a low risk of adverse procedure-related clinical complications.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…20 HydroCoils are safe, and initial procedural results from the HELPS study showed no significant difference in the complication rate in a properly controlled study. 21 This study agrees with ours in demonstrating a low risk of adverse procedure-related clinical complications.…”
Section: Discussionmentioning
confidence: 90%
“…[9][10][11][12][13][14][15][16][17][18][19] These same articles were recently the subject of an evidence-based review of bioactive coils by White and Raymond,20 which revealed that on the evidence-based hierarchy, the published data were inadequate, only achieving a Cochrane level C. The downfall of many of these studies as described by the authors of this latter publication was the inaccurate and incomplete reporting of data. We have attempted to overcome some of the deficiencies highlighted by the way we have reported our data.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic review of endovascular coiling of cerebral aneurysms by using coated coils demonstrated 4.7% and 2.9% morbidity-mortality rates in PGLA-coated and hydrogel-coated groups, respectively. 17 Immediate angiographic results of the HydroSoft coil were complete occlusion in 69%, residual neck in 19%, and residual sac in 12%. The HydroCoil Endovascular Aneurysm Occlusion and Packing Study showed complete immediate occlusion in 47% and residual neck in 31%.…”
Section: Discussionmentioning
confidence: 93%
“…Results of these new devices, however, are sometimes disappointing, and it remains to be proved that modified coils provide better results. [24][25][26] One of the limitations in our study, which began in 1998, is the absence of an independent core laboratory to analyze our results. However, in each of the 5 participating centers in our study, the physician who collected and reviewed all of the aneurysms was independent of the treating physician.…”
Section: Retreatmentmentioning
confidence: 99%